2008
DOI: 10.1002/elan.200704182
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Determination of the Antioxidant Capacity: The Ceric Reducing/Antioxidant Capacity (CRAC) Assay

Abstract: The CRAC assay is a direct electron transfer test of antioxidant capacity for several organic compounds. The ability of eight different compounds in reducing Ce 4þ was studied by chronoamperometric measurements of the remaining Ce 3þ species. The following antioxidant classification was observed: tannic acid ) quercetin > rutin > gallic acid % catechin > ascorbic acid > BHA > Trolox. These results agree with others already published and a good correlation (R 2 ¼ 0.937) was found with the classical spectrophoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…The following trend of variation of antioxidant capacities resulted from this comparative investigation, which relied on chronoamperometric measurements: tannic acid > quercetin > rutin > gallic acid ≈ catechin > ascorbic acid > butylated hydroxyanisole > Trolox. The results were consistent with those furnished by the applied conventional FRAP assay [236]. …”
Section: Significant Analytical Applications To Plant and Plant Exsupporting
confidence: 90%
“…The following trend of variation of antioxidant capacities resulted from this comparative investigation, which relied on chronoamperometric measurements: tannic acid > quercetin > rutin > gallic acid ≈ catechin > ascorbic acid > butylated hydroxyanisole > Trolox. The results were consistent with those furnished by the applied conventional FRAP assay [236]. …”
Section: Significant Analytical Applications To Plant and Plant Exsupporting
confidence: 90%
“…This comparative study led to the following trend of variation of antioxidant capacities: tannic acid > quercetin > rutin > gallic acid ≈ catechin > ascorbic acid > butylated hydroxyanisole > Trolox. The results are in agreement with those provided by previous studies, and the consistency with the classical FRAP assay was confirmed as well [118].…”
Section: Biamperometrysupporting
confidence: 92%
“…The Ceric Reducing Antioxidant Capacity (CRAC) assay was also investigated with respect to the direct electron transfer facility, for determining the antioxidant capacity of eight organic compounds, relying on their ability to reduce the oxidized form of the redox couple [118]. The proposed methodology consisted in following the reduction of the Ce 4+ concentration after its interaction, during 4 min, with the sample antioxidants.…”
Section: Biamperometrymentioning
confidence: 99%
“…The following trend of variation of antioxidant capacities resulted from this comparative investigation that relied on chronoamperometric measurements: tannic acid > quercetin > rutin > gallic acid ≈ catechin > ascorbic acid > butylated hydroxyanisole > Trolox. The results were consistent with those furnished by previous studies, and by the applied conventional FRAP assay [18].…”
supporting
confidence: 92%
“…The ceric reducing antioxidant capacity assay was also exploited by virtue of its direct electron transfer facility, for determining the antioxidant capacity of eight antioxidant compounds, also based on the capacity to reduce the oxidized form of the redox couple [18]. The developed technique was based on observing the decrease of the Ce 4+ concentration after its reaction with tested antioxidants.…”
mentioning
confidence: 99%